2011
DOI: 10.1007/s00120-011-2707-3
|View full text |Cite
|
Sign up to set email alerts
|

MRT-navigierte stereotaktische Prostatabiopsie

Abstract: Perineal stereotactic prostate biopsies guided by the combination of MRI and ultrasound allow effective examination of suspicious MRI lesions. Each biopsy core taken is documented accurately for its location in 3-D enabling MRI validation and tailored treatment planning. The morbidity of the procedure was minimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
3
0
3
Order By: Relevance
“…In a recent small study combining multiparametric MRI with TRUS, Kuru et al. reported a low AUR rate of 2% in 50 men after a median of 24 cores; however, using multiparametric MRI whilst not reducing number of biopsy cores is likely to increase cost. By contrast, our modified technique does not involve routine catheterisation and the 5.2% AUR rate is low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent small study combining multiparametric MRI with TRUS, Kuru et al. reported a low AUR rate of 2% in 50 men after a median of 24 cores; however, using multiparametric MRI whilst not reducing number of biopsy cores is likely to increase cost. By contrast, our modified technique does not involve routine catheterisation and the 5.2% AUR rate is low.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, catheter dependencies of 38–39% after TTSB have been reported, persisting in 1.6% of patients after 6 days . Others have combined multiparametric MRI and TTSB to minimise the AUR rate …”
Section: Introductionmentioning
confidence: 99%
“…In fusion US (FUS), real-time US images are simultaneously presented with corresponding images obtained from previously acquired CT or magnetic resonance (MR) images 10 . Reports have indicated that image fusion is valuable in cases of US-guided targeted ablation of liver and prostate tumors 11 12 13 . However, applications of image fusion to examine the musculoskeletal system have rarely been reported.…”
mentioning
confidence: 99%
“…Im Verlauf des stationären Aufenthalts wurde der transurethrale Dauerkatheter wieder entfernt und die Patienten im Anschluss entlassen.Jede Prozedur wurde softwareassistiert mit Hilfe des BiopSee TM Systems (Version 2.1 Medcom GmbH, Darmstadt) durchgeführt. BiopSee TM besteht aus einem Computer mit integrierter Software, sowie einem speziellen Ultraschallkopf zur transrektalen Anwendung, der während der Biopsie am Eingriffstisch fixiert ist und longitudinale und rotatorische Bewegungen zur Erfassung der Prostata zulässt(Kuru et al 2012). Zunächst wurden die transversalen MRT-Aufnahmen (T2 und DWI) in das System eingelesen und suspekte Läsionen, sofern auf Basis des MRT-Befundes vorhanden, eingezeichnet.…”
unclassified
“…Im nächsten Schritt erfolgte die Fusion. Mit Hilfe von BiopSee TM kann dabei aus einer Serie von transversalen TRUS-Bildern eine 3D Rekonstruktion der Prostata erstellt werden(Kuru et al 2012). Die eingelesenen MRT-Bilder werden mit dieser 3D Rekonstruktion der Prostata fusioniert(Kuru et al 2012).…”
unclassified